Modulated Light Elicitation and Associated Physiological and Molecular Processes in Phenolic Compounds Production in Ocimum basilicum L. Microgreens - Gabriel-Ciprian Teliban; Naomi-Eunicia Pavăl; Gabriela Mihalache; Marian Burducea; Vasile Stoleru; Andrei Lobiuc (Horticulturae)
Microgreens represent a valuable source of health-promoting compounds and also a research avenue, since such organisms have a very high plasticity related to environmental cues, allowing biotechnological development with low costs. Ocimum basilicum L. species naturally synthesize valuable, phenolic compounds, among which rosmarinic acid is most prominent. Within the current research, basil plantlets were grown for 10 days under either full spectrum light (white light) or modulated blue/red/far-red/UV spectrum elicitation with an additional factorization, by applying fertilization. Biomass accumulation reached up to 0.8 g/20 plantlets, while chlorophyll fluorescence was in the 0.75–0.78 range and remained uniform across treatments, indicating that no significant stress was exerted under modified light treatment. However, total phenolic contents and, in particular, rosmarinic acid contents, were markedly enhanced (up to 7.5 mg/g in the red cultivar) under modulated light treatment and fertilization, compared to full spectrum light. Moreover, in the red cultivar, gene expression was enhanced, 1.3–6.3 fold for genes coding for enzymes involved in phenylpropanoid synthesis pathways, such as phenylalanine ammonia lyase (PAL), tyrosine aminotransferase (TAT), Catechol-O-methyltransferase (COMT) and rosmarinic acid synthetase (RAS). Overall, light modulation coupled with fertilization led to the production of basil microgreens with up to 10% more total phenolics and up to 25% more rosmarinic acid. The results show that, using relatively simple growth equipment and setup, synthesis of health related, valuable compounds can be modulated in microgreens and, hence, serves as an avenue for businesses to develop cost effective biotechnological processes.